The Impact of Other Customers on Customer Citizenship Behavior - Yi, Youjae; Gong, Taeshik; Lee, Hyojin (Psychology & marketing, 2013)
ABSTRACT Despite extensive research on the antecedents of customer citizenship behavior, the influence of other customers remains a neglected area in service research. Drawing on social information processing and interpersonal influence theories, this article investigates how citizenship behavior of focal customers is shaped by citizenship behavior of other customers. This study also examines how informational influence in the form of other‐customer credibility and normative influence in the form of customer social identity moderate this relationship. Using qualitative and quantitative data, this study shows that other‐customer citizenship behavior drives focal customer citizenship behavior. This link is also moderated by informational influence (other‐customer credibility) and normative influence (social identity). From a theoretical standpoint, the findings provide preliminary evidence that other‐customer focus is critical to an understanding of customer citizenship behavior. This study also identifies the boundary conditions for these relationships. From a practical standpoint, the findings suggest that managers need to identify and pay attention to customers who exhibit citizenship behavior so that customer citizenship behavior is reciprocated and extended to other customers in the service encounter.